The Coordination of Gene Expression within Photosynthesis Pathway for Acclimation of C(4) Energy Crop Miscanthus lutarioriparius - Xing, Shilai (Front Plant Sci, 2016)
As a promising candidate for the second-generation C(4) energy crop, Miscanthus lutarioriparius has well acclimated to the water-limited and high-light Loess Plateau in China by improving photosynthesis rate and water use efficiency (WUE) compared to its native habitat along Yangtze River. Photosynthetic genes were demonstrated as one major category of the candidate genes underlying the physiological superiority. To further study how photosynthetic genes interact to improve the acclimation potential of M. lutarioriparius, population expression patterns within photosynthesis pathway were explored between one mild environment and one harsh environment. We found that 108 transcripts in assembled transcriptome of M. lutarioriparius were highly similar to genes in three Kyoto Encyclopedia of Genes and Genomes (KEGG) photosynthesis pathways of sorghum and maize. Phylogenetic analyses using sorghum, maize, rice, and Arabidopsis genes of dark reaction identified 23 orthologs and 30 paralogs of M. lutarioriparius photosynthetic genes. These genes were also clustered into two kinds of expression pattern. 87% of transcripts in dark reaction were up-regulated and all 14 chloroplast-encoded transcripts in light reaction increased degradation in the harsh environment compared to the mild environment. Moreover, 80.8% of photosynthetic transcripts were coordinated at transcription level under the two environments. Interestingly, LHCI and PSI were significantly correlated with F-ATPase and C(4) cycle. Overall, this study indicates the coordinated expression between cyclic electron transport (consisting of LHCI, PSI, and ATPase) and CO(2)-concentrating mechanism (C(4) cycle) could account for photosynthesis plasticity on M. lutarioriparius acclimation potential.